The sins of the fathers : a Matt Scudder mystery - Block, Lawrence, 1938- (Orion, 2000)
A pretty young girl is butchered in her Greenwich Village apartment.The prime suspect, a minister's son, is found dead in his jail cell and as far as the NYPD is concerned the case is closed.Matt Scudder, an ex-cop who now does 'favours for friends', is persuaded to look into the case by the dead girl's father.Suddenly he's up to his neck in sleaze and corruption, phoney religious cults and murderous lust.In New York's underbelly the children have no choice but to pay the price for their parents' most unspeakable sins.